PEMETAAN AIR TANAH MENGGUNAKAN METODE RESISTIVITAS WENNER SOUNDING (Studi Kasus Kampus II Universitas Islam Negeri Maulana Malik Ibrahim Malang) - Huda, A.M. Miftahul (Department of Physics, Maulana Malik Ibrahim State Islamic University of Malang, 2011)
Human is khalifa in this earth, it was presented at Qoran (Al-Fathir: 39). Then the earth is authority and responsibility of human to saving and managing. Include of that is aquifer. Aquifer is the water that is available in the throat of geology which permeable. The mapping of aquifer potency is important because it used for developing the collage II Islamic State University Maulana Malik Ibrahim of Malang at Junrejo, Batu. Good water is predicted consume at high level in future. This investigation purposefull to know the place of the potentiality of aquifer in the location of investigation verticality. The method used in this research is Resistivity Geoelectric is an used to investigate the current surface based on stone resistivity. In this case, is used wenner sounding configuration. potentiality of aquifer in the location of investigation verticality. At the every measuring using resistivity meter OYO Mc 2119. The result of the survey show if variety of depth and thick layers of aquifer; whit the best potentiality of aquifer at sounding point 2 C C (7° 55' 11,9